Informative advertising in a distribution channel - Shi, Hongyan (2020)
In this paper, we study how channel structure (decentralized vs centralized) and specified allocation of product advertising authority affect final advertising content and profits when consumers face uncertainty about both product match and retail price, and must incur a sunk cost to visit the retail store before making a purchase. We develop a game-theoretic framework in which a manufacturer and a retailer are defined as leader and follower, respectively, to model the strategic interactions and the optimal advertising and pricing decisions of channel members. In this context, we find that channel decentralization may lead to greater advertising content. Moreover, we find that if the manufacturer has product advertising authority additional to the retailer's product advertising authority, then both the product advertising provision and the price advertising provision can be greater. This additional product advertising authority can lead to the manufacturer's higher but the retailer's lower profit with increased overall channel profits. However, if the manufacturer has exclusive product advertising authority, as compared to the case in which both channel members can advertise product, the manufacturer's exclusive product advertising authority can lead to a decreased product advertising provision as well as a decreased price advertising provision; and it may even hurt the manufacturer while benefiting the retailer. We also find that a shift of exclusive product advertising authority from the retailer to the manufacturer leads to a product advertising provision that is such that more consumers will visit the store and purchase the product, which benefits the overall channel for a large parameter range.